2016
DOI: 10.1002/2015jc011482
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic assessment of erosion and flooding risk in the northern Gulf of Mexico

Abstract: 13-Sea-storm time series are simulated with a multivariate probabilistic model 14 -Erosion and flooding risk are assessed accurately with a joint probability approach 15 -Return water levels and impact hours could be larger than recently observed 16 Abstract 21We assess erosion and flooding risk in the northern Gulf of Mexico by identifying 22 interdependencies among oceanographic drivers and probabilistically modeling the resulting 23 potential for coastal change. Wave and water level observations are used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
86
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 30 publications
1
86
0
1
Order By: Relevance
“…Coastal inundation is associated with peak water level, not mean sea level, and depends on the combined effects of tides, storm surge, sea level variability, inland precipitation, river flow, and other factors which may lead to increases in extreme water level exceedance probabilities. This has been shown for many regions worldwide, including the Australian coasts (Haigh et al, ; Pugh & Woodworth, ), the United Kingdom (Svensson & Jones, , ), the Netherlands (Klerk et al, ), China (Lian et al, ), and the United States (Wahl et al, ). A more detailed listing of other studies that focus on compound factor coastal flooding is given in Table SM.2 in the supporting information of Moftakhari et al ().…”
Section: Introductionmentioning
confidence: 99%
“…Coastal inundation is associated with peak water level, not mean sea level, and depends on the combined effects of tides, storm surge, sea level variability, inland precipitation, river flow, and other factors which may lead to increases in extreme water level exceedance probabilities. This has been shown for many regions worldwide, including the Australian coasts (Haigh et al, ; Pugh & Woodworth, ), the United Kingdom (Svensson & Jones, , ), the Netherlands (Klerk et al, ), China (Lian et al, ), and the United States (Wahl et al, ). A more detailed listing of other studies that focus on compound factor coastal flooding is given in Table SM.2 in the supporting information of Moftakhari et al ().…”
Section: Introductionmentioning
confidence: 99%
“…In the bivariate case, many different copula families have proven to be useful (e.g., Salvadori et al 2014;Masina et al 2015, and references therein). For more than two oceanographic variables, nested (also called hierarchical) Archimedean copulas (Wahl et al 2012;Corbella and Stretch 2013;Lin-Ye et al 2016) and elliptical copulas, such as Gaussian or t, (Li et al 2014a;Wahl et al 2016;Rueda et al 2016) have been implemented and found valuable, but also dependence trees (Poelhekke et al 2016) and vines (De Michele et al 2007;Montes-Iturrizaga and Heredia-Zavoni 2016), which are a generalization thereof, have been proposed. Callaghan et al (2008) and Serafin and Ruggiero (2014) adopt two other approaches to model dependencies.…”
Section: A Vine-copula Model For Time Series Of Significant Wave Heigmentioning
confidence: 99%
“…Storm sequences (i.e., time series of storm events) have been modeled as different types of renewal processes (De Michele et al 2007;Callaghan et al 2008;Corbella and Stretch 2013;Li et al 2014b;Wahl et al 2016) often approximated by a triangle (Fig. 1) whose size is determined by a peak value and a critical threshold value of, for example, wave height or water level together with the storm duration (e.g., Boccotti 2000).…”
Section: A Vine-copula Model For Time Series Of Significant Wave Heigmentioning
confidence: 99%
“…Many simulation methods are based on renewal processes to model alternating sequences of storm and calm durations [8,9,10,11,12,13]. For the storm periods, high temporal resolution time series of the relevant metocean variables are then derived from an idealized 'storm shape'.…”
Section: Introductionmentioning
confidence: 99%
“…The above studies used different techniques to account for non-stationarities. The simplest approach has been to focus on the most important season [24] or to piecewise model seasons or months [26,12,4]. Other studies have used a superposition of linear or cyclic functions of time [17,19,21,9,7,27] and climate indices as co-variates [5,6,28,13] to represent trends or seasonal cycles on semiannual to decadal time scales.…”
Section: Introductionmentioning
confidence: 99%